Effectiveness of a Transesophageal Echocardiography Course. (November 2020) - Silva Restrepo, Marcos; Boivin, Michel A.; Kory, Pierre; Sarkar, Pralay K.; Banauch, Gisela I.; Halpern, Stephen; Mayo, Paul H.
Background: Transesophageal echocardiography has important applications for the management of the critically ill patient. There is a need to develop effective training programs for the critical care community in acquiring skill at critical care transesophageal echocardiography. Objective: We studied the effectiveness of a 1-day simulation-based course that focused on the acquisition of skill in the performance of critical care transesophageal echocardiography. Methods: Learners received training in image acquisition with a transesophageal simulator and training in image interpretation in small group sessions. Skill at image acquisition and image interpretation was assessed at the beginning and at the completion of the course. Results: There were 27 learners who attended the course. Pre and post knowledge scores were 55 (19; mean [SD]) and 88 (9; P < .0005), respectively. Pre and post image acquisition scores were 3.6 (3.7) and 9.9 (0.3; P < .0001), respectively. Conclusions: A 1-day course in critical care transesophageal echocardiography that combined case-based image interpretation with image acquisition training using a simulator improved technical skills and knowledge base.